PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR MURID DENGAN MODEL STAD BERBANTUAN EDUCAPLAY PADA MATERI BANGUN DATAR KELAS IVB DI SD NEGERI KALIWUNGU - Anindia Rahma Putri; Nur Ngazizah; Suyoto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the application of the STAD learning model assisted by Educaplay in improving student learning activity and learning outcomes in mathematics learning on plane shapes. It also examines the improvement in student learning activity and learning outcomes in mathematics learning on plane shapes. This study is a classroom action research (CAR) with two cycles consisting of planning, implementation, observation, and reflection. The subjects were 20 students of Grade IV of Kaliwungu State Elementary School. Data collection techniques included observation, interviews, tests, and documentation. Data analysis techniques used qualitative and quantitative analysis. The results of the study are: 1) The application of the STAD learning model assisted by Educaplay is very efficient in improving student learning activity and learning outcomes, especially in plane shapes. The results of the observation of the implementation of learning, cycle I was 78% categorized as very good and in cycle II, namely at the first meeting, 93% was very good. 2) The results of this study on student learning activity in the pre-cycle were 49% and cycle I was 61.75% with a good category, while in cycle II the meeting was 76.25%. categorized as good. 3) For student learning outcomes in the pre-cycle, 15% were categorized as very poor and in cycle I the first meeting was 55% categorized as good and in cycle II the first meeting was 85% with a good category. From the results of the observations above, it can be concluded that the application of STAD learning can improve student learning activity and learning outcomes.